(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article/essay carries out a methodological path that evokes the figurative image of the gods Minemosine and Terpsicore her daughter, patron of the art of dance, for the metaphorical unfolding of the creative qualities of the perceived feminine and narrated as a cosmic experience in the sense of a philosophical thought of cosmodance. This path includes the current context of remote choreographic creation, with technological mediation, in which bodily efforts face connection challenges. In this process there is a distension of the understanding of the presentation of the danced gesture, inaugurating several possibilities of recording, editing, presentation and storage of the image. In this movement between the mythical dimension, the incarnated experience and the technological universe the text is being developed in the discussion of cosmodansintermediations and cosmodansintersemiotizations and their alchemy in the cosmopolitical multiverse of dance.